Milk Fat Globule Epidermal Growth Factor 8 Attenuates Acute Lung Injury in Mice after Intestinal Ischemia and Reperfusion - Cui, Tianpen (American Thoracic Society, 2010)
Rationale: Milk fat globule epidermal growth factor 8 (MFG-E8) is a potent opsonin for the clearance of apoptotic cells and is produced by mononuclear cells of immune competent organs including the spleen and lungs. It attenuates chronic and acute inflammation such as autoimmune glomerulonephritis and bacterial sepsis by enhancing apoptotic cell clearance. Ischemia-reperfusion (I/R) injury of the gut results in severe inflammation, apoptosis, and remote organ damage, including acute lung injury (ALI). Objectives: To determine whether MFG-E8 attenuates intestinal and pulmonary inflammation after gut I/R. Methods: Wild-type (WT) and MFG-E8(−/−) mice underwent superior mesenteric artery occlusion for 90 minutes, followed by reperfusion for 4 hours. A group of WT mice was treated with 0.4 μg/20 g recombinant murine MFG-E8 (rmMFG-E8) at the beginning of reperfusion. Four hours after reperfusion, MFG-E8, cytokines, myeloperoxidase activity, apoptosis, and histopathology were assessed. A 24-hour survival study was conducted in rmMFG-E8– and vehicle-treated WT mice. Measurements and Main Results: Mesenteric I/R caused severe widespread injury and inflammation of the small intestines and remote organs, including the lungs. MFG-E8 levels decreased in the spleen and lungs by 50 to 60%, suggesting impaired apoptotic cell clearance. Treatment with rmMFG-E8 significantly suppressed inflammation (TNF-α, IL-6, IL-1β, and myeloperoxidase) and injury of the lungs, liver, and kidneys. MFG-E8–deficient mice suffered from greatly increased inflammation and potentiated ALI, whereas treatment with rmMFG-E8 significantly improved the survival in WT mice. Conclusions: MFG-E8 attenuates inflammation and ALI after gut I/R and may represent a novel therapeutic agent.